The Guidelines for Enhancing Customer Experience Of Don Mueang International Airport - Butrbumrungrak, Saruda; Khamproh, Thanyarat; Plangwattana , Warantri (Journal of Dhamma for Life, 2025)
This research aims to study the experiences of passengers who have used Don Mueang International Airport and to propose development strategies for enhancing passenger satisfaction throughout all stages of their journey from airport arrival, check-in, and document verification to in-terminal services in response to the increasing number of travelers. This is a quantitative research study utilizing a questionnaire to collect data from a sample of 439 Thai passengers who used Don Mueang Airport between 2020 and 2024. Descriptive statistics, including frequency, percentage, and mean, were used to analyze the data. The findings reveal that passenger experience is influenced by five key factors: (1) Physical such as convenience in space design and facility layout; (2) Subliminal including terminal atmosphere and environmental elements; (3) Communication the clarity and accessibility of information; (4) Human Interaction the responsiveness and supportiveness of airport staff, particularly in emergencies; and (5) Procedural the efficiency and simplicity of service processes. Recommendations for improvement include better space management, enhanced terminal atmosphere reflecting the airport's identity, staff training to ensure effective communication and privacy awareness, more efficient queue management, timely updates on gate or flight changes, and improved digital communication channels. These measures aim to elevate the overall passenger experience and strengthen Don Mueang Airport's competitiveness at an international level.